2012
DOI: 10.1161/strokeaha.112.660415
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score for Intracranial Hemorrhage in Patients With Acute Ischemic Stroke Treated With Intravenous Tissue-Type Plasminogen Activator

Abstract: Background and Purpose-There are few validated models for prediction of risk of symptomatic intracranial hemorrhage (sICH) after intravenous tissue-type plasminogen activator treatment for ischemic stroke. We used data from Get With The Guidelines-Stroke (GWTG-Stroke) to derive and validate a prediction tool for determining sICH risk. Methods-The population consisted of 10 242 patients from 988 hospitals who received intravenous tissue-type plasminogen activator within 3 hours of symptom onset from January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
218
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 212 publications
(231 citation statements)
references
References 22 publications
9
218
1
3
Order By: Relevance
“…One study reported a linear relation between admission glucose and an increase in the odds of sICH (OR 1.75 per 100 mg/dL increase in admission glucose) 5. Admission blood glucose levels were identified as a risk factor for sICH after intravenous tPA in several risk models for sICH post‐tPA 11, 25, 26, 27, 28. Although blood glucose is one of the potential modifiable factor in these risk scores, further studies are required to evaluate whether treatment of hyperglycemia reduces risk of sICH post‐tPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a linear relation between admission glucose and an increase in the odds of sICH (OR 1.75 per 100 mg/dL increase in admission glucose) 5. Admission blood glucose levels were identified as a risk factor for sICH after intravenous tPA in several risk models for sICH post‐tPA 11, 25, 26, 27, 28. Although blood glucose is one of the potential modifiable factor in these risk scores, further studies are required to evaluate whether treatment of hyperglycemia reduces risk of sICH post‐tPA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an increased risk of symptomatic intracranial hemorrhage (sICH) after tPA treatment in patients with diabetes or hyperglycemia,8, 9, 10 and admission glucose has been used in prognostic models to identify patients at risk of sICH after tPA 11. Even though studies did not find overall reduced benefit of tPA in diabetic patients,12 decreased rates of tPA administrations are observed in diabetic patients 13.…”
Section: Introductionmentioning
confidence: 99%
“…[140][141][142] Clinical Factors: Age, Hypertension, Hyperglycemia, and Hemorrhagic Transformation Increasing age has frequently been associated with an increased risk of HT in patients with stroke. 8,26,50,[143][144][145][146][147][148] The mechanisms by which age may contribute to HT are unclear. Age may enhance the production of ROS which promotes BBB disruption.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
“…151 Hypertension is also associated with an increased risk of HT in stroke patients. 8,[144][145][146]152,153 Acute elevations in blood pressure are presumed to directly affect BBB permeability and increase HT.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
See 1 more Smart Citation